Multiscale modeling of free-surface effect on crack formation in unidirectional off-axis laminates. (July 2017) - Kumagai, Yuta; Onodera, Sota; Nagumo, Yoshiko; Okabe, Tomonaga; Yoshioka, Kenichi
Abstract: A multiscale approach based on the mesh superposition method is applied to unidirectional CFRP laminates to evaluate the influence of the deformation field near the free-surface region on crack formation. Our approach employs two different scale analyses: local analysis utilizing a model composed of carbon fibers with micron-scale diameter and matrix resin, and global analysis employing a homogenized model assumed to be an anisotropic elasto-plastic body. Global analysis is conducted to evaluate the macroscopic deformation behavior of laminates. The local model is superimposed on the global model, maintaining the continuity of the displacement field between global and local domains. Local analysis is then performed to predict crack initiation and crack propagation, using the displacement field obtained from the global analysis. Our simulated results indicate that the initial crack occurring on the free-surface region does not affect the final failure strain.